A green history of the welfare state - Fitzpatrick, Tony, 1966- (Routledge explorations in environmental studies, 2017)
Environmental problems - particularly climate change - have become increasingly important to governments and social researchers in recent decades. Debates about their implications for social policies and welfare reforms are now moving towards centre stage. What has been missing from such debates is an account of the history of the welfare state in relation to environmental issues and green ideas. A Green History of the Welfare State fills this gap. How have the environmental and social policy agendas developed? To what extent have welfare systems been informed by the principles of environmental ethics and politics? How effective has the welfare state been at addressing environmental problems? How might the history of social policies be reimagined? With its lively, chronological narrative, this book provides answers to these questions. Through overviews of key periods, politicians and reforms the book weaves together a range of subjects into a new kind of historical tapestry, including: social policy, economics, party politics, government action and legislation, and environmental issues. This book will be a valuable resource for students and scholars of environmental policy and history, social and public policy, social history, sociology and politics.